Buyer-Supplier Social Capital, Supplier Integration, and Operational Supply Risk of SMEs Craft Batu Alam in Ngeposari, Semanu, Gunungkidul - Virliana Annida Luthfiani; Sabihaini Sabihaini; Yuli Liestyana (Journal of International Conference Proceedings, 2021)
This research aims to analyze the influence of buyer-supplier social capital on the operational supply risks with supplier integration as a mediation variable in natural stone craft SMEs in Ngeposari Village, Semanu Subdistrict, Gunungkidul Regency. Sampling techniques using nonprobability techniques with census methods are as many as 45 SME Natural stone craft in Ngeposari Village, Semanu Subdistrict, Gunungkidul Regency as respondents. The data collection method used is a questionnaire. The analysis tool used in this study used SmartPLS 3.2.9. The results showed that the buyer-supplier social capital affects the operational supply risk in SME Craft natural stone in Ngeposari Village, either directly or indirectly through supplier integration.